2012
DOI: 10.1080/13607863.2011.652594
|View full text |Cite
|
Sign up to set email alerts
|

‘She might have what I have got’: The potential utility of vignettes as an indirect measure of awareness in early-stage dementia

Abstract: For the participants with dementia, awareness was assessed in separate in-depth interviews and rated on a 5-point scale for comparison purposes.Results: Participants with dementia were often able to correctly identify the problems described in the vignettes, although scoring lower than carers or controls. Participants with dementia were also able to offer advice for those depicted, although to a lesser extent than carers or controls. Ability to offer advice was greater where MMSE scores were higher. For partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Unawareness of illness or its consequences, such as the cognitive or behavioural changes, is a common feature of AD [12,13], and it is plausible that stimuli about AD would produce a greater emotional reaction only in those with preserved awareness and who identify with the content of the material. Indeed, in connection with this, it has been shown that people with AD who have greater awareness of their own illness are more likely to provide appropriate advice when attempting problem solving vignettes concerning dementia [14]. Alternatively, it has been suggested that reactivity to illness material can be driven by implicit processing of information, bypassing explicit awareness of the effects of dementia [12,15].…”
mentioning
confidence: 99%
“…Unawareness of illness or its consequences, such as the cognitive or behavioural changes, is a common feature of AD [12,13], and it is plausible that stimuli about AD would produce a greater emotional reaction only in those with preserved awareness and who identify with the content of the material. Indeed, in connection with this, it has been shown that people with AD who have greater awareness of their own illness are more likely to provide appropriate advice when attempting problem solving vignettes concerning dementia [14]. Alternatively, it has been suggested that reactivity to illness material can be driven by implicit processing of information, bypassing explicit awareness of the effects of dementia [12,15].…”
mentioning
confidence: 99%
“…These findings were interpreted by the authors as the poor ability of people with AD to put themselves in someone else’s position. The authors explained that the different findings between their results and Clare et al (2012a) were attributable to methodological differences. Indeed, in Mograbi et al (2014), the cognitive demand of the task, where participants had to imagine themselves as someone else, was higher than in Clare et al (2012a), in which patients did have access to written vignettes.…”
Section: Relationship Between Metacognition and Perspective-takingmentioning
confidence: 86%
“…The authors explained that the different findings between their results and Clare et al (2012a) were attributable to methodological differences. Indeed, in Mograbi et al (2014), the cognitive demand of the task, where participants had to imagine themselves as someone else, was higher than in Clare et al (2012a), in which patients did have access to written vignettes. Altogether, these results suggest that patients with AD are more accurate when evaluating the performance of someone else (e.g., caregiver or fictional person) than they are for themselves.…”
Section: Relationship Between Metacognition and Perspective-takingmentioning
confidence: 86%
See 1 more Smart Citation
“…Using a vignette technique as an indirect method to assess awareness, Clare et al (2012) explored the ability of PwD (including AD, vascular dementia and mixed Alzheimer's and vascular dementia) to appreciate the deficits of a fictional person. PwD, their caregivers, and older adult controls were asked to identify and offer advice for the problems that were described in the vignettes.…”
Section: Metacognition and Perspective-taking In The Context Of Admentioning
confidence: 99%